The Effectiveness of Using the Scramble Method on the Efficiency in Mastering of vocabulary for the Arabic Language (Students of the Seventh Grade D in the Islamic At-Taufiqiyah Secondary School) - Ramadhan, Yusfar; Septiana, Syavita (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
AbstrakThe scramble method is a group learning process by matching the question cards and answer cards that have been provided by the teacher according to the questions and is one of the language games that can acquire certain skills in a fun way. By implementing this method it can make it easier for students to understand Arabic vocabulary, so that an increase in students' understanding can be seen during the learning process. The purpose of this study was to find out how the process of implementing the scramble method was and to find out how effective the use of the scramble method was on the Arabic vocabulary comprehension skills of students in class VII â€œDâ€ MTs Pondok Pesantren At-Taufiqiyah Aeng Bajaraja Bluto Sumenep 2020/2021 Academic Year. This research uses a quantitative approach with the type of Quasi Experiment research using the Nonequivalent Control Group Design research design. Based on the results of the calculation of learning outcomes data obtained -â„Žig(18.851) >- (2.040) Then seen from the significance level is 0.000 which indicates a significance of 0.000 <0.05. This indicates that 0 is rejected and 1 is accepted. From the explanation above it can be concluded that there is a significant effectiveness between the use of the scramble method on the skill of understanding Arabic vocabulary. 0.05. This indicates that 0 is rejected and 1 is accepted. From the explanation above it can be concluded that there is a significant effectiveness between the use of the scramble method on the skill of understanding Arabic vocabulary. 0.05. This indicates that 0 is rejected and 1 is accepted. From the explanation above, it can be concluded that there is a significant effectiveness between the use of the scramble method on the skill of understanding Arabic vocabulary.